RESPONSE OF GROWTH AND YIELD OF INDUSTRIAL BOTATOES TO SOIL IMPROVEMENT AND SPRAYING WITH TOCOPHEROL AND TREHALOSE UNDER WATER STRESS - Abdul Karim H. Sh. Al-Rubaie; Kadhim D. H. Al-Jubouri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the response of the growth and yield of industrial potatoes (Solanum tuberosum L.) to the addition of soil improvement and spraying with tocopherol, The field experiments were carried out during the fall season 2020-2021 and the spring 2021 at one of the fields at the area located at 44.23° longitude and 33.32° latitude, The experiments carried out as a factorial experiment within a split plot design, where the irrigation interval factor was set every 4, 8 and 12 days for the fall season and every 4, 7 and 10 days for the spring season (symbolized by I0, I1 and I2) in the main plot, and the interaction factor between Eco Gel soil improver and anti-stress spray in the Sub plot with three replications, as Eco Gel was added to the soil at the level of 50 kg ha-1 symbolized by E1 and added to the level of 100 kg ha-1 symbolized by E2 as well as the treatment without adding that Its symbol is E0, and spraying with anti-stress, tocopherol with a concentration of 30 mg L-1 symbolized by T1 and trehalose with a concentration of 30 mmol L-1 symbolized by T2, as well as spraying with normal water symbolized by T0, the results showed a significant superiority for the treatment of the triple interaction I1E2T2 in percentage increase Nitrogen, phosphorous, potassium, plant length, total leaves and total tubers, yield per plant and total yield for the two seasons, respectively, compared to treatment I2 E0T0.